Heat transfer rate characteristics of two-phase closed thermosyphon heat exchanger. (November 2021) - Song, Wei; Zheng, Changjin; Yang, Jiaming
Abstract: Two-phase closed thermosyphon heat exchangers (TPCTs) have considerable potential for use in ground source heat pump systems. This paper proposes a new metal-polyethylene TPCT that uses water as the working fluid and is composed of a galvanized steel pipe and a polyethylene pipe. The heat transfer rate characteristics of the metal-polyethylene TPCT were studied using a constant-temperature water bath test bench. The experimental results show that the metal-polyethylene TPCT has the best heat transfer rate when the vacuum degree and filling ratio are 1.00 kPa and 12.5%, respectively. The average heat transfer rate increased as the temperature of the heat source and the flow rate of the cooling water increased. Finally, a sandbox test bench was built, which provided seepage and non-seepage experimental conditions for the metal-polyethylene TPCT. In the sandbox experiment, the heat transfer rate capacity of the metal-polyethylene TPCT was initially studied and compared with that of a single U-tube heat exchanger, and the heat transfer rates were similar. When the evaporation section length was 0.5 m, the heat transfer rates were 34.89 W/m and 111.75 W/m under non-seepage and seepage conditions, respectively. The experimental results show that the metal-polyethylene TPCT is feasible as a new type of ground heat exchanger. Graphical abstract: Image 1 Highlights: A two-phase closed thermosyphon ground heat exchanger (TPCT) is proposed. Constant temperature water baths (CTWBs) and sandbox test benches were constructed. The heat-transfer characteristics of the TPCT were tested using the CTWBs. The average heat transfer rate of the TPCT was 34.89 W/m on the sandbox test bench. The heat transfer rate of the TPCT was approximately 80% of that of a U-tube.